2010
DOI: 10.1111/j.1469-8137.2010.03450.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of abscisic acid and water stress in root herbivore‐induced leaf resistance

Abstract: Summary• Herbivore-induced systemic resistance occurs in many plants and is commonly assumed to be adaptive. The mechanisms triggered by leaf-herbivores that lead to systemic resistance are largely understood, but it remains unknown how and why root herbivory also increases resistance in leaves.• To resolve this, we investigated the mechanism by which the root herbivore Diabrotica virgifera induces resistance against lepidopteran herbivores in the leaves of Zea mays.• Diabrotica virgifera infested plants suffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
112
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 104 publications
(116 citation statements)
references
References 54 publications
4
112
0
Order By: Relevance
“…In addition, to what extent the increased concentrations are the result of reduced root water contents is currently unclear. As BXDs have an important role in plant defense and protection against herbivores and pathogens (Ahmad et al., 2011; Glauser et al., 2011; Maag et al., 2016), the drought‐induced concentration increase may also alter plant interactions with other plant‐associated organisms (Erb et al., 2011; Robert et al., 2012). …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, to what extent the increased concentrations are the result of reduced root water contents is currently unclear. As BXDs have an important role in plant defense and protection against herbivores and pathogens (Ahmad et al., 2011; Glauser et al., 2011; Maag et al., 2016), the drought‐induced concentration increase may also alter plant interactions with other plant‐associated organisms (Erb et al., 2011; Robert et al., 2012). …”
Section: Discussionmentioning
confidence: 99%
“…The fact that WCR attack further accentuated the delay in silk emergence points to a further increase in drought stress in WCR‐attacked plants. Small maize seedlings were shown previously to suffer from increased leaf water loss upon combined drought and WCR attack (Erb et al., 2011). Potential interactive effects between water deficit and WCR attack have also been noted episodically in the field (Godfrey, Meinke, & Wright, 1993; Urías‐López, Meinke, Higley, & Haile, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the production of many HIPVs, particularly terpenoids, depends on plant photosynthesis (Paré and Tumlinson 1997), it is possible that the observed phenomenon is not adaptive per se, but simply the result of a physiological constraint, as has been observed for other aspects of plant-insect interactions (Erb et al 2010). The fact that linalool was also suppressed during the night, however, suggests that the suppression also occurs independently of the plant's photosynthetic activity.…”
Section: The Suppression Of Vocs Reduces Intraspecific Competitionmentioning
confidence: 91%
“…For example, tannins are considered especially important in defence against specialist insects as digestibility-reducing compounds [9,10]. Damage by above-ground and/or below-ground herbivores may affect the levels of primary and secondary metabolites in plants, and changes in these chemicals can mediate the interactions of above-ground and below-ground herbivores [11][12][13][14][15]. For instance, Kaplan et al [11] found in tobacco that root-feeding nematodes increased the performance of folivorous caterpillars by blocking synthesis of alkaloids that are transported to leaves, but caterpillars increased nematode performance by increasing nitrogen transport to roots.…”
Section: Introductionmentioning
confidence: 99%